2008
DOI: 10.1007/s10517-008-0036-3
|View full text |Cite
|
Sign up to set email alerts
|

Structural and mechanical characteristics of erythrocyte membranes in patients with type 2 diabetes mellitus

Abstract: The morphology and structure of erythrocyte cytoskeleton and local mechanical characteristics in patients with type 2 diabetes mellitus and donors were studied by atomic force microscopy. Poikilocytosis and anisocytosis, spatial reorganization of the cytoskeleton (loosening and condensation of the actin-spectrin network), and modification of local mechanical properties of erythrocytes were characteristic of diabetics. These results indicate significant heterogeneity of erythrocyte population in the patients, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Structural and biochemical changes of RBC that cause alterations in the cytoskeleton proteins may lead to degradation of the cell. Modifications like glycation and oxidation of spectrin have been documented in diabetes mellitus and associated to erythrocyte membrane changes [26][27]. We recently could demonstrate glycosylation and proteolytic cleavage of spectrin in RBC of VL patients [11].…”
Section: Introductionmentioning
confidence: 79%
“…Structural and biochemical changes of RBC that cause alterations in the cytoskeleton proteins may lead to degradation of the cell. Modifications like glycation and oxidation of spectrin have been documented in diabetes mellitus and associated to erythrocyte membrane changes [26][27]. We recently could demonstrate glycosylation and proteolytic cleavage of spectrin in RBC of VL patients [11].…”
Section: Introductionmentioning
confidence: 79%
“…Baines in 2009 suggested that the elasticity of RBCs depends on the dynamic rearrangement of spectrin dimers/tetramers under the shearing forces experienced in circulation (Baines, 2009); and that stable intact helical linker regions are needed to maintain the soft elasticity of spectrin (Mirijanian and Voth, 2008). A decreased deformability is also seen in inflammatory conditions such as diabetes (Shin et al, 2007); a spatial reorganization of the cytoskeleton was also noted in this condition (Starodubtseva et al, 2008). A reduced plasticity in cerebral ischemia (Kowal, 1996) and increase stiffness was also noted in conditions like coronary disease and hypertension (Lekka et al, 2005).…”
Section: Discussionmentioning
confidence: 92%
“…66,67 RBCs play a fundamental role in the inflammatory process including having a changed deformability, rheology or sedimentation rate. 53,65,[67][68][69][70][71][72][73][74][75][76][77][78][79][80] Central to cardiovascular health is the optimal functioning of RBCs, and central to a variety of vascular and degenerative diseases is the presence of poorly liganded iron [81][82][83] some of which comes from erythrocytes, and which leads to a variety of morphological and phenotypic manifestations. Therefore in this review, we will be taking an integrative approach that focuses on the use of biophysical properties of RBCs and fibrin(ogen) as diagnostic indicators of health.…”
Section: Introductionmentioning
confidence: 99%